Physics-based characterization of lambda sensor output to control emissions from natural gas fueled engines - Toema, Mohamed Ahmed (Kansas State University, 2010)
The increasingly strict air emission regulations may require implementing Non-Selective Catalytic Reduction (NSCR) systems as a promising emission control technology for stationary rich burn spark ignition engines. Many recent experimental investigations that used NSCR systems for stationary natural gas fueled engines showed that NSCR systems were unable to consistently control the exhaust emissions level below the compliance limits. Part of this thesis is devoted to show the results from the field testing of three engines working in natural gas gathering stations located in the “Four Corners” area. These three engines are retrofitted with NSCR systems. Emissions and engine operating data were monitored for more than one year. Data collected from October 2007 through December 2008 shows significant variation in emissions levels over hours, days, and longer periods of time, as well as seasonal variations. As a result of these variations, simultaneous control of NOx and CO below the compliance limit was achieved less than fifty percent of the monitored time. Modeling of NSCR components to better understand, and then exploit, the underlying physical processes that occur in the lambda sensor and the catalyst media is now considered an essential step toward improving NSCR system performance. The second portion of this thesis focuses on modeling the lambda sensor that provides feedback to the air-to-fuel ratio controller. Correct interpretation of the sensor output signal is necessary to achieve consistently low emissions level. The goal of this modeling study is to improve the understanding of the physical processes that occur within the sensor, investigate the cross-sensitivity of various exhaust gas species on the sensor performance, and finally this model serves as a tool to improve NSCR control strategies. This model simulates the output from a planar switch type lambda sensor. The model consists of three modules. The first module models the multi-component mass transport through the sensor protective layer. Diffusion fluxes are calculated using the Maxwell-Stefan equation. The second module includes all the surface catalytic reactions that take place on the sensor platinum electrodes. All kinetic reactions are modeled based on the Langmuir-Hinshelwood kinetic mechanism. The third module is responsible for simulating the reactions that occur on the electrolyte material and determine the sensor output voltage. The details of these three modules as well as a parametric study that investigates the sensitivity of the output voltage signal to various exhaust gas parameters is provided in the thesis.
Keywords: Lambda Sensor; Modeling; Engineering, Mechanical (0548)